2023
DOI: 10.1002/adma.202301901
|View full text |Cite
|
Sign up to set email alerts
|

A Gas/phototheranostic Nanocomposite Integrates NIR‐II‐Peak Absorbing Aza‐BODIPY with Thermal‐Sensitive Nitric Oxide Donor for Atraumatic Osteosarcoma Therapy

Abstract: Photothermal therapy (PTT) has received increasing interest in cancer therapeutics owing to its excellent efficacy and controllability. However, there are two major limitations in PTT applications, which are the tissue penetration depth of lasers within the absorption range of photothermal agents and the unavoidable tissue empyrosis induced by high‐energy lasers. Herein, a gas/phototheranostic nanocomposite (NA1020‐NO@PLX) is engineered that integrates the second near‐infrared‐peak (NIR‐II‐peak) absorbing aza‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Studies have found that the human body also generates endogenous H 2 S and participates in cell activities, such as autophagy, apoptosis, and proliferation, and is involved in regulating multiple signaling pathways, with antioxidant, anti-inflammatory, anti-tumor, and other activities [39][40][41][42]. Similar to NO and CO [43][44][45][46][47], H 2 S tends to play a role in inducing vasodilation, cell protection, and anti-inflammatory at low concentrations and shows a cancer-promoting effect in tumor cells. H 2 S exhibits a "bell model" in its effects on tumor cells that is, it exhibits a cancer-promoting effect at a relatively lower concentration and a cancer-inhibiting effect at a relatively higher concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that the human body also generates endogenous H 2 S and participates in cell activities, such as autophagy, apoptosis, and proliferation, and is involved in regulating multiple signaling pathways, with antioxidant, anti-inflammatory, anti-tumor, and other activities [39][40][41][42]. Similar to NO and CO [43][44][45][46][47], H 2 S tends to play a role in inducing vasodilation, cell protection, and anti-inflammatory at low concentrations and shows a cancer-promoting effect in tumor cells. H 2 S exhibits a "bell model" in its effects on tumor cells that is, it exhibits a cancer-promoting effect at a relatively lower concentration and a cancer-inhibiting effect at a relatively higher concentration.…”
Section: Introductionmentioning
confidence: 99%